Analisis Pelanggaran Kode Etik Anggota KPPS pada Pilgub Sumbar Tahun 2020 - Sumarni, Sumarni; Zetra, Aidinil; Putri, Indah Adi (Indonesian Democracy Research Center, 2023)
The phenomenon of voting ballots with a pen carried out by voters at TPS 1 in Salak Village, Sawahlunto City, in the 2020 West Sumatra Governor Election caused problems with the performance of KPPS officers. KPPS members were declared to have violated the code of ethics and received a written warning from the KPU of Sawahlunto City. This study aims to describe the process by which members of the KPPS violated the code of ethics at TPS 1 Salak Village and analyze the causal factors. Data analysis uses the theories of election fraud and election malpractice. This research uses a qualitative descriptive approach with a case study method. The results showed that the KPPS violated the code of ethics at TPS 1 in Salak Village due to: The KPPS members' non-compliance with the rules, namely,